Three-dimensional analysis of temperature field for various parameters affect the film cooling effectiveness - Bayraktar, Seyfettin; Yilmaz, Tamer (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this paper, a lot of parameters that affect the film cooling performance have been investigated numerically in three-dimensional model. For this purpose, five different inclination angles (alpha = 30 degrees, 45 degrees, 60 degrees, 75 degrees and 90 degrees), four blowing ratios (M = 0.2, 0.5, 1.0, 2.0) two different nozzle geometries, namely, circular and square shaped have been considered for multiple nozzles. Renormalized (RNG) k-epsilon turbulence model is used as turbulence closure. The performance of RNG k-epsilon turbulence model is tested by comparing with available experimental data found in the literature and it is observed that both results are in good agreement. Based on series of simulations it can be concluded that maximum cooling efficiency is obtained at inclination angle of 30 degrees and the blowing ratio of 2.0. It should be noted that circular shaped nozzle provides more effective cooled surface than square shaped nozzles. Present paper shows also the dependence of the cooling efficiency to the one of the most important vortex structure of counter-rotating vortex pair. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Film cooling; Turbulent flow; Computational fluid dynamics; Navier-Stokes equations; Inclined jet; Free-stream; Cross-flow; LEADING-EDGE; HEAT-TRANSFER; 2 ROWS; NUMERICAL-SIMULATION; FLOW; HOLES; JET; ANGLES; PLATE; Thermodynamics; Energy & Fuels; Mechanics